Impact of community-based rehabilitation on attainment of sustainable development goals: The case of selected districts in Zimbabwe - Pasara, Michael Takudzwa (Frontiers in Communication, 2022)
Several factors including droughts, cyclones, COVID-19 and inconsistent economic policies compounded to challenges faced by children and persons with disabilities (PwDs) in rural areas of Zimbabwe. Consequently, there was higher risk of low quality of life, poverty and limited access to basic services such as education and health. Various community based rehabilitation (CBR) programs were implemented to address violation of rights and access to services and participation by PwDs in general. This study used a mixed methods approach to analyse the impact of CBR programs taking into account the United Nations Convention of Rights of Persons with Disabilities (UN-CRPD) five themes: education, health, livelihoods, social protection and participation. Respondents included core beneficiaries, caregivers, teachers, community health workers and other key stakeholders. Results indicated that 61% were female respondents and 39% were males. Approximately, 84% of rural families survive on less than USD 20.00 per month with the modal household having 5 to 9 members per household. Cognitive levels are generally higher with 81% having received at least secondary education although some did not complete Ordinary Level. However, had tertiary education. The reach of CBR was high as 92% of respondents received training on disability management; 71% on income generating projects (IGPs) and 84% on Internal Savings and Lending (ISAL) although only 32% received funding. The study recommends funding for self-help groups, increased technical support, functional disability friendly toilets and orthopaedic centres, scaling up of programs at national level and adoption by the relevant ministry(ies), decentralisation by government officials to reduce red-tape and accelerate programs, training of trainers for additional capacity building. Improved latitude for NGOs and consistent economic policies are also needed to sustain IGPs.